PRACTICAL CONSIDERATIONS FOR THE DESIGN OF AUTONOMOUS MOBILE ROBOTS - KELLY, KEVIN (My University, 2012)
This paper addresses the practical challenges that engineers encounter when designing autonomous mobile robots. The issues faced are multi -disciplinary in nature and become exponentially more co mplex as the behavioural diversity and robustness requirements of the robot are in creased. In response to the need for a highly effective generalised suite of pr inciples to aid the design of autonomous machines, a set of eight practical desi gn guidelines are proposed. These principles directly complement the embodied design principles which represent one of the most complete design methodologies developed to date. The effectiveness of these principles is qualitatively assessed through direct comparison of a robot platform designed using these principles with an analogous platform which was not.
29th International Manufacturing Conference
Keywords: design; robotics